Klasyfikacja, ujmowanie, wycena i ujawnianie nieruchomości inwestycyjnych według MSSF - Cińcio, Donata (Classification, disclosure, measurement and presentation of investment property based on IFRS, 2008)
This report describes classification, disclosure, measurement and presentation of investment property based on International Financial Reporting Standards. This subject is elaborated in IAS 40 Investment Property. The standard states that investment property is property held to earn rentals or for capital appreciation or both, but is not held for use in the production or supply of goods or services or for administrative purpose; or sale in the ordinary course of business. During IAS 40 investment property must be initially measured at cost, including transaction costs and after initial measurement the standard permits entities to choose either: a fair value model or a cost model. One chosen method must be adopted for all of a company's investment property but change is permitted only if this results in a more appropriate presentation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 11-19